Regulation of Telomere Length Requires a Conserved N-Terminal Domain of Rif2 in Saccharomyces cerevisiae. Issue 2 (20th August 2015) - Kaizer, Hannah; Connelly, Carla J; Bettridge, Kelsey; Viggiani, Christopher; Greider, Carol W
Abstract: The regulation of telomere length equilibrium is essential for cell growth and survival since critically short telomeres signal DNA damage and cell cycle arrest. While the broad principles of length regulation are well established, the molecular mechanism of how these steps occur is not fully understood. We mutagenized the RIF2 gene in Saccharomyces cerevisiae to understand how this protein blocks excess telomere elongation. We identified an N-terminal domain in Rif2 that is essential for length regulation, which we have termed BAT domain for B locks A ddition of T elomeres. Tethering this BAT domain to Rap1 blocked telomere elongation not only in rif2 Δ mutants but also in rif1 Δ and rap1C-terminal deletion mutants. Mutation of a single amino acid in the BAT domain, phenylalanine at position 8 to alanine, recapitulated the rif2 Δ mutant phenotype. Substitution of F8 with tryptophan mimicked the wild-type phenylalanine, suggesting the aromatic amino acid represents a protein interaction site that is essential for telomere length regulation.